Identifying patterns in the fatty-acid composition of safflower depending on agroclimatic conditions - Tultabayev, Mukhtar; Chomanov, Urishbay; Tultabayeva, Tamara; Shoman, Aruzhan; Dodaev, Kuchkar; Azimov, Utkir; Zhumanova, Umyt (Eastern-European Journal of Enterprise Technologies, 2022)
The object of the study reported in this paper is to establish a dependence of the fatty acid composition of the fast-growing annual plant safflower on the agroclimatic cultivating conditions. The growth rate of safflower and the characteristics of the extracted oil are highly dependent on external temperature and moisture. At low temperatures, for example, the growth of safflower is significantly inhibited. With an increase in temperature and the length of daylight, the central stem begins to branch while growing faster. Flowering is mainly affected by the length of daylight. The period from the end of flowering to maturity is typically 28‒30 days. However, the total ripening period of the crop depends on the variety, location, sowing time, and agro-climatic cultivating conditions. The need for water increases significantly during the flowering period of safflower, which ultimately affects the indicators of the fatty acid composition and yield. At the same time, safflower is sensitive to moisture in terms of disease. In case of excess water, it is subject to root rot. In addition, frequent rains and high humidity after ripening can provoke the germination of seeds on the head. Hence, it follows that in order to obtain a high yield with the specified characteristics of the fatty acid composition of safflower oil, it is necessary to take into consideration the quantitative indicators of moisture and its seasonality, as well as the temperature regime during the growing season. The study was conducted using arid or semi-arid, sharply continental Central Asia with its hot summers and cold winters as an example. The dependence of the physicochemical parameters of plant-derived oils on agroclimatic indicators has been established. The reported results and conclusions will allow farmers to predict the yield of oilseeds with specified characteristics depending on the changing climatic parameters